The secret and the real: contemporary pathways to the autobiographical and life writing (Philology, 2026)
The article explores some of the major theoretical and critical tendencies that follow the problems surrounding autobiographical studies, as well as other genres of life writing during the last decades. The study is based on those subject-specific arguments and objectives that are archetypal for life writing, namely self-knowledge and contextualizing in the world, and offers a short historical overview of the practices of examining personal identity. Among these, we find examples of life writing that are not meant to be published, but represent a way of self-confirmation for the subject.The study also raises the question of drawing the line of demarcation between autobiographical and pseudo-autobiographical writings—a question that is fundamental to the common use of terms like “autobiography,” as well as juxtaposing fiction and reality (or fiction and document). Focusing on the changeable nuances of the taxonomy itself and considering both the conceptualization and the concepts that researchers like Lejeune, de Man, Starobinski, Gusdorf, Doubrovsky, Abbott, Beaujour, and Maran use to denote life writing, the article formulates the archetypal paradoxes in defining intimacy and delineates the difficulties that other studies face when dealing with life writing in general.
Keywords: autobiography; life writing; intimacy; autobiographical genres